2003
DOI: 10.1063/1.1631388
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes on supercooling liquid silicon

Abstract: X-ray diffraction experiments and ab initio molecular dynamics (AIMD) simulations have been performed to investigate the atomic structure of liquid silicon into the deeply supercooled region. The levitation technique used has made it possible to extend the measurements down to a temperature of 1458 K, 230 K below the equilibrium melting point. The x-ray and AIMD results, which are in reasonable agreement, show conclusively that the tetrahedral order is reinforced and that the coordination number decreases as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
72
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 41 publications
13
72
2
Order By: Relevance
“…For direct comparison, the results of previous x-ray measurements are reproduced in Fig. 3(b) [7][8][9]. For liquids, the first shell coordination number is poorly defined, and several methods for determining N can be found in the literature [16].…”
mentioning
confidence: 60%
See 3 more Smart Citations
“…For direct comparison, the results of previous x-ray measurements are reproduced in Fig. 3(b) [7][8][9]. For liquids, the first shell coordination number is poorly defined, and several methods for determining N can be found in the literature [16].…”
mentioning
confidence: 60%
“…3, the data clearly show a constant coordination number of approximately 6:0 0:5 over the entire temperature range from above T M down to a supercooling of 316 K. Our results for the temperature independence of the coordination number are in conflict with the results of several previously published experimental studies and with expectations from most simulation studies based upon the SW potential. Using the conical nozzle technique for sample levitation and diffraction measurements for x rays in the energy range of 7-25 keV, Ansell et al [7] and Jakse et al [8] have reported that the coordination number decreases with decreasing temperature. Working in a reflection geometry using relatively low energy x rays requires significant data corrections for the scattering geometry as well as absorption and multiple scattering.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the temperature dependences of the coordination number for some nonmetallic amorphous materials have been studied by several groups. [12][13][14] Ansell et al [12] and Jakse et al [13] reported the coordination number decreases with decreasing temperature for supercooled liquid silicon, while Kim et al [14] presented evidence to emphasize the temperature independence of the coordination number for the same material. In this work, local atomic structures at glassy, supercooled liquid, and liquid states for La 62 Al 14 Cu 11.7 Ag 2.3 Ni 5 Co 5 BMG are investigated by in-situ high-temperature X-ray diffraction (XRD).…”
Section: Qk Jiang Zy Chang Xd Wang and Jz Jiangmentioning
confidence: 99%